An Investigation of Self-reported Health-related Productivity Loss in Office Workers and Associations With Individual and Work-related Factors Using an Employer's Perspective - Pereira, M.; Johnston, V.; Straker, Leon; Sjøgaard, G.; Melloh, Markus; O Leary, S.; Comans, T. (Lippincott Williams and Wilkins, 2017)
Objective: Office workers have a high prevalence of musculoskeletal conditions. This can be a significant economic burden due to health-related productivity loss. Individual and work-related factors related to office worker health-related productivity were investigated. Methods: A survey including the Health and Work Performance Questionnaire, which estimated productivity loss, also recorded individual and work-related factors with potential associations with health-related productivity. Muscle function and workstation ergonomics were examined through physical assessments. Linear models investigated the relationships between these factors and health-related productivity. Results: Significant factors identified were occupational category (0.001<P<0.050), job satisfaction (P<0.001), psychological wellbeing (P=0.031), and musculoskeletal pain (P=0.023). Health-related productivity loss was greater in office workers working as managers, with lower job satisfaction and psychological wellbeing, and those with musculoskeletal pain. Conclusion: Office worker health-related productivity loss is represented by a combination of both individual and work-related factors.